The hospital environment as an ecological driver of multidrug-resistant organisms: evidence from intensive isolation and operating rooms - Widyasari, Domas Fitria; Daniwijaya, Edwin Widyanto; Purnomo, Galih Santo; Rahayu, Ayu; Nuryastuti, Titik (Berita Kedokteran Masyarakat, 2026)
Purpose: Multidrug-resistant organisms (MDROs) present a significant challenge for hospital infection control, with environmental surfaces acting as key reservoirs. This study sought to identify MDRO species, evaluate their biofilm-forming capacity, and quantify microbial bioburden in intensive care isolation and operating rooms. Methods: Environmental sampling was conducted in 16 rooms. Air and surface samples, including floors, walls, and bedside monitors, were collected using a microbiological air sampler and sterile swabs. Samples were cultured to determine total bioburden and detect MDROs, with bacterial identification performed using VITEK 2. Antimicrobial resistance was assessed using the Kirby-Bauer disc diffusion test, and bioburden levels were compared to national standards. Results: Forty-nine MDRO isolates were identified: 3 methicillin-resistant Staphylococcus aureus (MRSA, 6.12%), 19 methicillin-resistant coagulase-negative staphylococci (MRCONS, 38.78%), 24 carbapenem-resistant Acinetobacter spp. (CRA, 48.98%), and 3 extended-spectrum β-lactamase (ESBL)-producing Enterobacterales (6.12%). Mean microbial bioburden remained within acceptable limits for air (57.44 CFU/m³), walls (70.63 CFU/100 cm²), and bedside monitors (22.63 CFU/100 cm²), but exceeded thresholds on floors (753.75 CFU/100 cm²). Biofilm-forming capacity varied: MRCONS (26.32% strong biofilm), CRA (8.33% strong biofilm), and ESBL-producing Enterobacterales (66.67% weak biofilm). Conclusion: MDROs were detected in all sampled rooms, with CRA as the predominant species. Floors exhibited microbial loads above acceptable standards, highlighting the necessity for improved cleaning protocols. Enhanced environmental infection control strategies are essential to reduce MDRO transmission in healthcare settings.